Pharmacokinetic and Pharmacodynamic Insights into Vaitarana Basti: An HPTLC-Based Interpretation with Clinical Validation - Dr. Akshay Kumar; Dr. Divya B (The Bioscan, 2026)
Vaitarana Basti is a classical medicated enema indicated in Amavata (rheumatoid arthritis) and other Vata-Kapha dominated disorders, yet its behavior in terms of modern pharmacokinetics and pharmacodynamics has remained largely theoretical. In the present work, a methanolic extract of Vaitarana Basti (start and end samples) was subjected to high-performance thin-layer chromatography (HPTLC) on silica gel 60 F₂₅₄ plates, with densitometric scanning at 254 nm and 366 nm. Distinct Rf bands were observed in both UV ranges, which were tentatively correlated with phenolic acids, flavonoids, lignans, coumarins, sterols and fatty acid fractions derived mainly from Tamarindus indica pulp and Sesamum indicum oil [1][2][3][4]. On the basis of published pharmacology of these phytochemical classes and available experimental data on medicated enemas, a composite picture emerges: phenolic and flavonoid components likely undergo partial systemic absorption through the rectal mucosa, while lipophilic lignans and fatty acids contribute to local mucosal protection, modulation of inflammatory mediators and improved penetration of co-constituents [5][6][7][8]. These findings offer a mechanistic bridge between traditional Vaitarana Basti indications and contemporary concepts of drug disposition and tissue-level action. Clinical validation was demonstrated through a case of seropositive rheumatoid arthritis showing 69.7% reduction in CRP levels and 50% reduction in pain scores following 8-day Karma Basti protocol [9].